2005
DOI: 10.1167/iovs.04-0756
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Vasodynamic Changes in Light and Darkness in Smokers

Abstract: The normal capacity for increased blood flow velocity in the central retinal artery in darkness was markedly reduced in smokers. This finding may explain the reduced dark vision after recent smoking reported in several studies and probably reflects the combined effects of an increased blood viscosity, the vasoconstrictive action of nicotine, and a reduced capacity of the blood to transport oxygen, as the hemoglobin is partly occupied by carbon monoxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 33 publications
(24 reference statements)
0
26
0
1
Order By: Relevance
“…First, smoking mediates a substantial amount of their systemic toxicity though increased systemic reactive oxygen species [34–37]. Second, blood flow studies find decreased retinal blood flow due to increased vascular resistance [3840], which may exert further pressure on the age-related increased metabolic load on RPE cells.…”
Section: Discussionmentioning
confidence: 99%
“…First, smoking mediates a substantial amount of their systemic toxicity though increased systemic reactive oxygen species [34–37]. Second, blood flow studies find decreased retinal blood flow due to increased vascular resistance [3840], which may exert further pressure on the age-related increased metabolic load on RPE cells.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Human retinal blood flow velocity has been reported to be lower in light compared with dark as measured by laser Doppler velocimetry. 39 There are considerably more studies that reported higher activities in light compared with dark in the inner retina. Human retinal blood flow, which is tightly coupled to increased neural activity in the retinal vessels, has been reported to increase (~37%) from dark to light.…”
Section: Discussionmentioning
confidence: 99%
“…31 Hay evidencia de que la exposición a luz muy intensa puede producir daño en el ojo inmaduro. 32 Niveles altos de iluminación han sido asociados a resultados clínicos negativos: menor ganancia de peso, comportamentales y alteraciones en el desarrollo del sueño, además de estrés en pacientes muy prematuros o gravemente enfermos. 7,24,[33][34][35] El cambio brusco en la cantidad de luz también afecta al neonato: Shogan y Schumann 36 reportaron caídas rápidas de saturación en grandes prematuros al aumentar de manera repentina la iluminación.…”
Section: Efectos De La Luz Sobre La Fisiología Y El Desarrollo Del Neunclassified